2001
DOI: 10.1007/s002280100375
|View full text |Cite
|
Sign up to set email alerts
|

Effect of influenza vaccination on serum clozapine and its main metabolite concentrations in patients with schizophrenia

Abstract: Influenza vaccination using conventional trivalent influenza vaccine does not affect serum concentrations of clozapine or its main metabolites. However, an infection-related increase in CRP may be associated with increased serum concentration of clozapine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 18 publications
2
29
0
Order By: Relevance
“…Raaska et al found a non-significant increase of CRP in a group of 12 schizophrenic patients after influenza vaccination and highest levels of CRP at day 2 [18]. CRP was measured before and 2, 4, 7 and 14 days after vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Raaska et al found a non-significant increase of CRP in a group of 12 schizophrenic patients after influenza vaccination and highest levels of CRP at day 2 [18]. CRP was measured before and 2, 4, 7 and 14 days after vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies suggested highest increases of CRP in the first week after vaccinations [12,18]. We therefore measured CRP at baseline and 2, 3, 4 and 5 days thereafter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was recently highlighted by Raaska et al, who reported an increase in clozapine serum concentration in two patients who developed minor infections [76]. In all these cases, cytokine plasma levels were linked to the reduction of P450-dependent drug clearance.…”
Section: Discussionmentioning
confidence: 84%
“…Such a concept was clearly defined in a recent article by Raaska et al, who pointed out that a minor infection could also modify drug metabolism, thus creating a clinical condition similar to those described for vaccine-drug interactions [76].…”
Section: Discussionmentioning
confidence: 97%